Propagation of Rubber Tree Resistant to White Root Disease through Somatic Embryogenesis from Thin Cell Layer and Floral Explants and Assessment of Somaclonal Variation by RAPD and SSR Markers - Kanjanee Tongtape (Prince of Songkla University, 2023)
Thesis (Ph.D., Plant Science)--Prince of Songkla University, 2022